Bam Archaeological Mission: a new archaeological research programme in Kerman Province, Iran. (27th June 2018) - Mutin, Benjamin; Garazhian, Omran
Abstract : The Bam Archaeological Mission aims to investigate ancient settlement in the Bam-Narmashir region of Iran. Preliminary survey has identified over 200 new archaeological sites, with renewed excavation at the key site of Tell-e Atashi revealing structural evidence of Neolithic occupation.